FACTORS RELATED TO COMPLIANCE WITH HYPERTENSION PATIENTS IN THE TREATMENT OF TREATMENT - Nurbaya Nurbaya; Subakir Subakir; Ratna sari Dewi (Jurnal Riset Kesehatan, 2020)
Hypertension that is continuously high for a long time can cause complications. Therefore, hypetension must be detected early with routine blood pressure checks. This study aims to determine the factors associated with compliance with hypertension in undergoing treatment in the work area of Simpang Tuan Health Center. This study uses a cross sectional design. The study sample was 168 people with hypertension. The sampling technique is proportional random sampling. The instrument used was a questionnaire with interviews. Data were tested using the chi square statistical test. The results showed that 89.3% of respondents had low adherence to treatment, 44.6% had poor knowledge, 29.8% had poor attitudes, 77.4% had poor access to services, 50% had poor family support , 32.7% of the role of health workers is not good. The results of bivariate analysis found that there was a relationship between knowledge (p = 0,000), access to services (p = 0.014) and compliance with hypertension in undergoing. There was no relationship between attitude (p = 0.119) and family support (p = 0.803) and the role of health workers (p = 0.203) with hypertension patients' compliance in undergoing treatment at the Simpang Tuan Health Center in 2020. Community Health Center provides health education to hypertensive sufferers outpatient care at Simpang Tuan Health Center and health education should not only be given to hypertension sufferers, but also to families and people closest to hypertension sufferers so that they can participate in reminding and motivating hypertensive sufferers